Interaction of photothermal graphene networks with polymer chains and laser-driven photo-actuation behavior of shape memory polyurethane/epoxy/epoxy-functionalized graphene oxide nanocomposites. (24th October 2019) - Punetha, Vinay Deep; Ha, Yu-Mi; Kim, Young-O; Jung, Yong Chae; Cho, Jae Whan
Abstract: This work demonstrates the fabrication and near infra-red laser-driven shape recovery actuation behavior of bisphenol A diglycidyl ether-functionalized graphene oxide (DGEBA-f-GO)-based polyurethane (PU)/epoxy nanocomposites. DGEBA-f-GO was synthesized as a photothermal filler by treating DGEBA with carboxylated GO in a two-step process. Homogeneously dispersed networks of the photothermal filler were engineered via covalent crosslinking between DGEBA and DGEBA-f-GO in the PU matrix. The crosslinked DGEBA-f-GO networks act as a near-infrared laser-harvesting framework for the efficient transfer of heat and trigger for shape recovery upon remote actuation. Interaction between the photo-thermal networks of DGEBA-f-GO with polymer chains was analyzed structurally, revealing that the DGEBA-f-GO networks in the nanocomposites stimulate the formation of an integrated netpoint framework in the matrix by interacting with the PU hard segment via hydrogen bonding. Consequently, the shape memory composites reinforced with GO networks showed enhanced laser-driven photo-actuation stress, as well as thermal stability, photothermal behavior, and mechanical properties. Graphical abstract: Image 1 Highlights: Remote actuation in graphene networks containing polyurethane/epoxy nanocomposites. The near-infrared laser-harvesting and remote actuation by engineering the photothermal networks in the polymer matrix. The composites exhibited enhanced actuation stress and better mechanical properties. Graphene based photothermal networks stimulate the formation of an integrated net-point framework in the matrix.